(untitled) (Journal of actual problems of jurisprudence, 2018)
This article discloses the content of the institution of citizenship. The authors consider that citizenship is the most important legal institution that determines the legal status of a person. At the same time, it is emphasized that the legal regulation of citizenship is carried out by each state independently. The purpose of this article is to reveal the common in the legal regulation of the institution of citizenship, inherent in all states and special, on the example of the Republic of Kazakhstan and the United Kingdom. When writing the work, both general theoretical and specifically scientific methods of cognition were used, namely dialectical, comparative, legal, historical, formally dogmatic (specifically, legal), specifically legal and logical. The scientific and practical significance of the research lies in the results and conclusions. Increased scientific interest in the problem of citizenship is associated with migration of the population. This migration process has increased dramatically in recent years due to armed conflicts and economic decline in some countries. This study emphasizes that the legal regulation of citizenship must correctly reflect the migration processes in order to anticipate negative consequences for both the state and the individual in the state. It has been revealed and justified that the legislation on the citizenship of Kazakhstan and the UK provides for a number of requirements for obtaining citizenship. This article reveals two main ways of obtaining citizenship: by birth and by residence or by naturalization. In the legislation on the citizenship of Kazakhstan and the United Kingdom, there is a specially prescribed legal procedure for obtaining citizenship. The authors, based on the analysis of Kazakhstan’s legislation, distinguish the following ways of obtaining citizenship: by birth; As a result of naturalization; On the basis of interstate agreements of Kazakhstan; On the grounds provided by the Law of Kazakhstan “On Citizenship”. An analysis of UK legislation, namely the British Citizenship Act of 1981, showed that there are the following ways of obtaining citizenship: – by birth; – by origin; Through naturalization and registration. On the basis of the scientific approach to the question of citizenship and its role in the existence of the state, it is concluded that bipatrizm (multiple citizenship) adversely affects the state and carries a large risk to the state, including leading to the loss of independence and sovereignty. The practical value of the article is the possibility of using the results obtained to improve the constitutional legislation of the Republic of Kazakhstan, in law enforcement activities when obtaining or denying citizenship. Key words: Constitution, citizenship, naturalization, deprivation of citizenship, migration, renunciation of citizenship, acquisition of citizenship, bipatrism.